Optimalisasi Pemanfaatan Dana Desa Terhadap Pembangunan di Desa Tanjungsari, Kecamatan Pacitan, Kabupaten Pacitan - Aida Fatma; Lego Karjoko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The use of Village Funds does not always go according to plan and optimally. Tanjungsari Village has become one of the villages with the largest Village Fund income in the last two years. This research aims to look at the optimization of the use of Village Funds carried out by the Tanjungsari Village government as a manifestation of the implementation of Law number 6 of 2014 concerning Villages. The research method used in this research is descriptive analysis method with a qualitative approach. The results of this research are divided into three, the first is that the Village Fund has been utilized by Tanjungsari Village for village development and community empowerment in accordance with the priorities for utilizing Village Funds based on directions from the central government. Second, the use of Village Funds in Tanjungsari Village has provided many benefits for the people of Tanjungsari Village which are in accordance with the objectives of the Village Fund. Third, the use of Village Funds in Tanjungsari Village has not been running optimally because the use of Village Funds is still unable to solve the problem of unemployment and poverty and significantly increase original village income in Tanjungsari Village.